Psychometric properties of the child PTSD checklist in a community sample of South African children and adolescents. - Boyes, M; Cluver, L; Gardner, F (Public Library of Science, 2012)
OBJECTIVE: The current study assessed the basic psychometric properties of the Child PTSD Checklist and examined the structure of symptoms of posttraumatic stress disorder (PTSD) in a large sample of South African youth. METHODOLOGY: The checklist was completed by 1025 (540 male; 485 female) South African youth (aged between 10 and 19 years). The factor structure of the scale was assessed with a combination of confirmatory and exploratory techniques. Internal consistencies for the full scale and all subscales were evaluated with Cronbach's alpha and McDonald's omega. Validity was assessed by comparing PTSD scores obtained by children who had and had not experienced a traumatic event, and by examining associations between total PTSD scores and known correlates of PTSD. RESULTS: Scores on the Child PTSD Checklist clearly discriminated between youth who had experienced a traumatic event and those who had not. Internal consistencies for the full scale (and all subscales) were acceptable to good and hypothesized correlations between PTSD, depression, anxiety, somatic symptoms, and age were observed. Two of the reported fit statistics for the tripartite DSM-IV-TR model of PTSD did not meet traditional criteria and further exploratory analyses revealed a four-factor structure (broadly consistent with Simms and colleagues' Dysphoria Model of PTSD symptoms) which provided a better fit to the observed data. CONCLUSION: Given the continued use of the Child PTSD Checklist in South Africa, findings offer an important first step in establishing the reliability and validity of the checklist for use with South African youth. However, further evaluation of the checklist in South African samples is clearly required before conclusions regarding its use as diagnostic tool in this context can be made.